Too big to fail: The transatlantic debate - Morris Goldstein; Nicolas Véron (Bruegel, 2011)
Although the United States and the European Union were both seriously impacted by the financial crisis of 2007, the resulting policy debates and regulatory responses have differed considerably on the two sides of the Atlantic. In this paper the authors examine the debates on the problem posed by 'big to fail' financial institutions. They identify variations in historical experiences, financial system structures, and political institutions that help one understand the differences in the approaches of the US, EU member states, and the EU institutions in addressing this problem. The authors then turn to possible remedies and how they may be differentially implemented in America and Europe. They conclude on the policy developments that are likely in the near future.
Keywords: G01; G21; G38; F36; 330; banks; comparative political economy; financial regulation; microprudential policy; too-big-to-fail; Bankenregulierung; Finanzmarkt; Regulierung; Großbank; EU-Staaten; USA